QEXAFS and UV/Vis Simultaneous Monitoring of the TiO2-Nanoparticles Formation by Hydrolytic Sol-Gel Route - Stoetzel, Jan; Luetzenkirchen-Hecht, Dirk; Frahm, Ronald; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Kaminski, Renata; Fonda, Emiliano; Villain, Francoise; Briois, Valerie (Amer Chemical Soc, 2010)
The hydrolysis of titanium(IV) tetraisopropoxide and the following condensation and aggregation to titania nanoparticles under slow water solution addition were concomitantly investigated by in situ QEXAFS and UV/vis spectroscopies The amount of dominant utanate species in the solution was determined as a function of time. Impel attire. and water addition rate Resulting from last hydrolysis and condensation of isopropoxide precursors an intermediate oligomeric species is initially formed at the early stages of the reaction This oligomeric species has been identified as a dodecatitanate species with Ti11O13 or Ti12O16 molecular framework. At the subsequent stage of the reaction corresponding to slower processes compared to the fast hydrolysis, titania nanoparticles are formed by a cluster-cluster growth mechanism involving the consumption of the dodecatitanate species following a pseudo first-order reaction Finally, at the advanced stage, sudden aggregation of mania nanoparticles occurs at a given threshold of amount of nanoparticles